Effects of Anthropogenic Noise on Animals (Springer Handbook of Auditory Research,, 2018)
This volume examines the effect of man-made sound on animals, with a focus on vertebrates. · Man-Made Sounds and Animals Hans Slabbekoorn, Robert J. Dooling, and Arthur N. Popper · Communication Masking by Man-Made Noise Robert J. Dooling and Marjorie R. Leek · The Principles of Auditory Object Formation by Nonhuman Animals Micheal L. Dent and Mark A. Bee · Characteristics of Temporary and Permanent Threshold Shift in Vertebrate James C. Saunders and Robert J. Dooling · Acoustic Conditions Affecting Sound Communication in Air and Underwater Ole Næsbye Larsen and Craig Radford · Effects of Man-Made Sound on Fishes Anthony D. Hawkins and Arthur N. Popper · Effects of Anthropogenic Noise on Amphibians and Reptiles Andrea Megela Simmons and Peter M. Narins · Impact of Man-Made Sound on Birds and Their Songs Wouter Halfwerk, Bernard Lohr, and Hans Slabbekoorn · Effects of Man-Made Sound on Terrestrial Mammals Hans Slabbekoorn, JoAnn McGee, and Edward J. Walsh · Effects of Noise on Marine Mammals Christine Erbe, Rebecca Dunlop, and Sarah Dolman Hans Slabbekoorn is Associate Professor in the Department of Behavioural Biology at Leiden University Robert J. Dooling is Professor in the Department of Psychology at the University of Maryland Arthur N. Popper is Professor Emeritus and research Professor in the Department of Biology at the University of Maryland, College Park Richard R Fay is Distinguished Research Professor of Psychology at Loyola University Chicago.